Amebic liver abscess in northern region of Bangladesh: sociodemographic determinants and clinical outcomes - Alam, Faisal; Salam, Md. Abdus; Hassan, Pervez; Mahmood, Iftekhar; Kabir, Mamun; Haque, Rashidul (BioMed Central, 2014)
Background: Amebic liver abscess (ALA) is endemic in Bangladesh since historical age but its epidemiology and sociodemographic determinants are not well described in the literatures. This paper focuses on the endemicity, sociodemographic determinants and clinical outcomes of ALA patients from certain northern districts in Bangladesh. Ninety hospitalized ALA patients enrolled from 6 northern districts of Bangladesh during July 2008 to June 2010 were analyzed. Findings: Clinical presentations of ALA was initially substantiated by ultrasound imaging and later confirmed by detection of small subunit rRNA gene of E. histolytica using a Real Time PCR. Structured questionnaire and data sheet were used to record sociodemographic characteristics, clinical presentations and outcomes. Patients were followed for immediate and late treatment outcomes up to 2 years since diagnosis. Northern districts those situated on the Ganges basin were noted as endemic areas. Male significantly outnumbered the female with a male to female ratio of 21:1 and majority of patients (58%) were in their 3rd and 4th decades. A significant (21%) number of patients were aborigines despite their ethnic minority as population under investigation and overall 68% belonged to low socioeconomic group. Habit of indigenous alcohol consumption was very high (78%) among ALA patients with overwhelming majority was illiterate (74.44%) and from rural population (70%). Fever with right hypochondriac pain of variable duration was the principal presenting complains. Gross fluid derangements including pleural effusion, edema and ascities were observed in 39% cases and 6% had rupture of abscess. All patients were treated with standard antimicrobial regimen and discharged with initial recovery. Recurrent attack was observed in 6% cases and 3 (3.33%) patients died during 2 years follow-up period. Complicated (37.78%) ALA patients showed significant Odds ratio (P < 0.05) for major sociodemographic determinants in comparison to non-complicated patients. Conclusions: Amebic liver abscess is endemic in certain northern districts of Bangladesh especially on the Ganges basin with relatively high prevalence among aborigines. Rural habitat, ethnicity (Aborigine) and habit of indigenous alcohol consumption were found to be strong determinants, especially for complicated ALA, which were associated with different grades of morbidity and a few mortalities.